URGENSI EVALUASI PEMBELAJARAN DALAM PENDIDIKAN - Fachri, Moh (JURNAL EDURELIGIA, 2018)
Learning process is the most important part in education as an effort to mature learners, The success of the learning process becomes a benchmark achievement of learning objectives. To know the achievement of the success of learning objectives, it must be done evaluation / assessment. In particular the purpose of evaluation to determine the progress of learning outcomes of learners after following the learning, as well as to determine the level of effectiveness and efficiency of methods, strategies that teachers use in learning. Evaluation of learning has an important and strategic meaning in education, because the learning process becomes meaningful, as well as its evaluation results can be used as a basis to determine the next step, for teachers, principals, institutions, parents, and government. The importance of learning evaluation can be seen from the approach of the learning process, the characteristics of professional educators, and the institutional approach, but it can also be seen from its purpose, function and principles and the validity and reliability of its evaluation tool.